The Restructuring of the Romanian Higher Education System - Văcărescu Hobeanu, Loredana (Journal of Research in Educational Sciences; Vol 1 No 2 (2010): JRES, Volume I, Issue 2(2), Winter 2010, 2010)
The legislative and institutional reform in the education is topical in our country, starting from the Bologna Declaration and from the results of subsequent meetings of ministers who are responsible for the higher education. With the signing of the Bologna Declaration and with the agreement creating the European Higher Education Area, Romania is committed to a long process of change. The undergone transformations from the Romanian education and from the higher education generally and in particular since 1990, the accession of our country to the European, required the conceptual and structural changes to make it compatible with the requirements of an effective education in which the recognition of the diplomas be covered with skills and competencies.